Answered

Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Y = 2x + 3

X Y
-3
-1
2
4
5


Sagot :

y=2x+3
for x = -3 y = 2*(-3)+3=-6+3=-3
for x = -1 y = 2*(-1)+3=-2+3=1
for x = 2 y = 2*2+3 = 4+3 = 7
for x = 4 y = 2*4+3 = 8+3 =11
for x = 5 y = 2*5+3 = 10+3 =13
AyaZ
[tex]Y = 2x + 3 \\ \\ x=-3 \\ Y = 2(-3) + 3=-6+3=-3\\ \\ x=-1 \\ Y = 2(-1) + 3=-2+3=1\\ \\ x=2 \\ Y = 2(2) + 3=4+3=7\\ \\ x=4 \\ Y = 2(4) + 3=8+3=11\\ \\ x=5 \\ Y = 2(5) + 3=10+3=13[/tex]